Ovicidal and larvicidal effects of spinosad in Aedes aegypti (Diptera: Culicidae) - ARGUETA, ANA L.; VALLE, JAVIER; MARINA, CARLOS F. (Revista Colombiana de Entomología, 2011)
The ovicidal and larvicidal effects of spinosad were studied in Aedes aegypti treated with concentrations of 0.1, 5 y 10 ppm spinosad (Tracer 480SC) during different periods of exposure at a constant temperature of 25±1ºC. In a first experiment the ovicidal effects were low (6.6-8.2% of non-eclosion averaged over 12-96h exposure periods), whereas in a second experiment ovicidal effects were moderate (27,9 - 31,9% of non-eclosion in eggs exposed to spinosad suspension of 1-12 weeks old). Mortality of larvae increased significantly with increasing concentration and increasing duration of exposure to this product. Although spinosad has clear applications as a mosquito control product for control of vectors such as A. aegypti, it is clear that its vector control potential resides in its larvicidal effects rather than its ovicidal activity.